2018
DOI: 10.1248/bpb.b17-00724
|View full text |Cite
|
Sign up to set email alerts
|

AMPK-Mediated Regulation of Lipid Metabolism by Phosphorylation

Abstract: AMP-activated protein kinase (AMPK) is a metabolic sensor in mammals that is activated when ATP levels in the cell decrease. AMPK is a heterotrimeric protein that comprises 3 subunits, each of which has multiple phosphorylation sites that play critical roles in the regulation of either anabolism or catabolism by directly phosphorylating proteins or modulating gene transcription in multiple pathways, such as synthesis, oxidation and lipolysis of lipid. Research focused on the phosphorylation sites that are invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
162
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(163 citation statements)
references
References 82 publications
0
162
0
1
Order By: Relevance
“…The LDL receptor is regulated through sterol regulatory elementbinding protein 2 (SREBP-2), which has an important role in hepatic cholesterol homeostasis (Hua et al, 1993). SREBP-2 is down-regulated by AMP-activated protein kinase α (AMPKα) (Wang et al, 2018), and a recent study found enhancement of AMPKα expression in D-allulosefed rats (Chen et al, 2019). These findings suggest the possibility that D-allulose might down-regulate the LDL receptor by suppression of SREBP-2 through enhancement of AMPKα expression.…”
Section: Discussionmentioning
confidence: 99%
“…The LDL receptor is regulated through sterol regulatory elementbinding protein 2 (SREBP-2), which has an important role in hepatic cholesterol homeostasis (Hua et al, 1993). SREBP-2 is down-regulated by AMP-activated protein kinase α (AMPKα) (Wang et al, 2018), and a recent study found enhancement of AMPKα expression in D-allulosefed rats (Chen et al, 2019). These findings suggest the possibility that D-allulose might down-regulate the LDL receptor by suppression of SREBP-2 through enhancement of AMPKα expression.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, mTORC1 signaling was regulated in a tissue‐dependent manner by a ketogenic diet (Roberts et al, ). Like TOR, AMPK is a metabolic sensor that regulates the synthesis, oxidation, and lipolysis of lipids (Wang, Liu, Zhai, Zhang, & Tian, ). In the mouse study which showed that FAT10 knockout mice live longer, the authors noted that these mice had increased AMPK activity in skeletal muscle (Canaan et al, ).…”
Section: Lipid‐related Aging Mechanismsmentioning
confidence: 99%
“…Another signal potentially involved in lipotoxicity-mediated tubular damage is the AMPK-PGC-1α pathway. As this pathway activity decreases, an increase in the intra-cytoplasmic triglyceride synthesis and accumulation is observed [151]. PGC-1α, a key regulator of mitochondrial biogenesis and energy metabolism, is proposed as one of the main therapeutic targets in acute kidney damage, CKD, and DN [152][153][154][155][156][157].…”
Section: Lipotoxicity In Renal Cellsmentioning
confidence: 99%